Excess Return of US Mutual Funds - N. V. Artamonov; A. N. Kurbatskii (Vestnik MGIMO-Universiteta)
The paper examines the factors that contribute to the outperformance of mutual funds in relation to the market, with a particular emphasis on the macroeconomic indicators as the key variables of interest. The paper begins by providing a comprehensive literature review on various factors that can impact the performance of mutual funds. The discussion encompasses a wide range of topics, including skill presence, diseconomies of scale, and other challenges associated with generating excess returns for investors.In the second part of the paper, an empirical analysis is conducted using actively managed US mutual funds to establish a relationship between fund performance and macro-variables, specifically focusing on term and credit spreads. Furthermore, the study considers different returns on positive and negative changes in spreads. The sample consists of funds that primarily invest in various sectors within the United States, with the Standard and Poor's 500 (S&P 500) serving as the benchmark. To assess the performance of funds with active strategies, panel data models are applied, with the excess return over the benchmark as the dependent variable. Different subperiods, including the financial crisis and the COVID-19 period, are examined. Notably, the impact of variables during the pandemic period differs significantly from other subperiods. The findings indicate that positive and negative changes in the spread between corporate bond yields have significant and positive effects across almost all periods, which has practical implications for potential investors. It suggests that active professional portfolio managers have been successful in uncertain periods. To control for external shocks and funds' cross-correlation, double-clustered standard errors are employed, and a series of robustness checks confirm the stability of the results.